2012
DOI: 10.4103/0019-5049.103964
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in paediatric neuraxial blocks

Abstract: Paediatric anaesthesia and paediatric regional anaesthesia are intertwined. Almost all surgeries unless contradicted could be and should be supplemented with a regional block. The main objective of this review is to elaborate on the recent advances of the central neuraxial blocks, such as application of ultrasound guidance and electrical stimulation in the pursuit of safety and an objective end point. This review also takes account of the traditional technique and understand the benefits as well the risk of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
8
0
3
Order By: Relevance
“…Our anaesthesia plan was to maintain spontaneous ventilation with the face mask[ 4 ] and ultrasonography (USG)-guided caudal block. [ 5 ] The pros and cons of caudal block were discussed with parents as per our routine.…”
mentioning
confidence: 99%
“…Our anaesthesia plan was to maintain spontaneous ventilation with the face mask[ 4 ] and ultrasonography (USG)-guided caudal block. [ 5 ] The pros and cons of caudal block were discussed with parents as per our routine.…”
mentioning
confidence: 99%
“…Although caudal block is partly easy and safe, block failure is the most common complication. Recently, many studies have shown that ultrasound-guided caudal block can help to improve the success rate and decrease the number of attempts [ 7 ]. However, skills training is necessary for the use of ultrasound in regional anesthesia, and ultrasound-guided caudal block may not feasible in all clinics due to its high cost.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound imaging for neuraxial blockade is easier to perform in the pediatric population compared to adults because of the shallower depth to structures of interest, which permits use of higher‐frequency ultrasound probes with superior imaging resolution . Although some studies demonstrate an advantage of using ultrasound guidance for spinal anesthesia in adults, ultrasound guidance is primarily used for limb, epidural, and caudal blockade in children . No published reports exist that describe ultrasound guidance for intrathecal injection in pediatric patients for management of chronic pain …”
Section: Discussionmentioning
confidence: 99%